The terror years from al-Qaeda to the Islamic State - Wright, Lawrence 1947- (A Borzoi book, 2016)
"Eleven powerful pieces first published in The New Yorker recall the path terror in the Middle East has taken from a more peaceful time in 1990s Israel to the recent beheadings of reporters by ISIS.With the Pulitzer Prize-winning The Looming Tower, Lawrence Wright became generally acknowledged as one of our major journalists writing on terrorism in the Middle East. This collection draws on several articles he wrote while researching that book as well as many that he's written since, following where and how Al Qaeda and its core cult-like beliefs have morphed and spread. They include: a picture of Saudi Arabia under the control of the religious police; the Syrian film industry, then compliant at the edges but already exuding a feeling of the barely masked fury that erupted into civil war; Israel and Hamas waging war over Gaza. Others continue to look into Al-Qaeda as it forms a master plan for its future, experiences a rebellion from within the organization, and spins off a growing web of terror in the world. The American response is covered in profiles of two FBI agents and a head of the CIA. It ends with the recent devastating capture and beheadings by ISIS of four American journalists and how our government handled the situation"...